Cardiovascular risk factors in students at a public college institution in Brazil - Thiago Ferreira de Sousa; Mariana da Silva Ferreira; Sueyla Ferreira da Silva dos Santos; Silvio Aparecido Fonseca; Aline Rodrigues Barbosa; Sandra Celina Fernandes Fonseca (Hospital de Clínicas de Itajubá, 2021)
Objective: To compare the prevalence of cardiovascular risk factors in university students from a Brazilian public higher education institution between three surveys. Methods: Cross-sectional surveys were conducted with 1,084, 1,085, and 1,041 university students in 2010, 2012, and 2014, respectively, from an institution located in Bahia, Brazil. Outcomes were cardiovascular risk factors: overweight, leisure-time physical activity for < 150 min per week, low consumption of fruits and vegetables, consumption of meat and chicken with fat, fried snacks, soft drinks or artificial juices, smoking, drinking alcohol abuse, and negative self-assessment of stress in life. The independent variable was the year of the survey.The measure of association was the Prevalence Ratio (PR). The significance level was 5%. Results: In all surveys, there was a higher prevalence of college students with insufficient leisure-time physical activity, low consumption of fruits and vegetables, consumption of fatty and savory meat, and negative self-assessment of stress. Overweight and consumption of chicken with fat increased over the years of the survey. Prevalence decreased in the last survey among college students concerning the consumption of fruits, vegetables, snacks, and artificial soft drinks or juices (PR: 0.66; 95% CI: 0.52-0.84). Conclusions: There was an increase in overweight; however, there were also positive modifications in eating habits among college students.